Respostas
respondido por:
10
{[(32+3) ÷ 7 +(3+3) · 3] · 2 –(12)÷ 6} · 2 + 12=
{[5+18]· 2 – 2} · 2 + 12=
{46-2} · 2 + 12=
88+12=
100
{[5+18]· 2 – 2} · 2 + 12=
{46-2} · 2 + 12=
88+12=
100
respondido por:
0
Resposta:
{[(8•4+3)÷7+(3+15÷5)•3]•2-(19-7)÷6}•2+12
{[(32+3)÷7+(3+3)•3]•2-12÷6}•2+12
{[35÷7+6•3]•2-2}•2+12
{[5+18]•2-2}•2+12
{23•2-2}•2+12
{46-2}•2+12
44•2+12
88+12
= 100
Explicação passo a passo:
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás